The nationwide Finnish anticoagulation in atrial fibrillation (FinACAF): study rationale, design, and patient characteristics - Lehto Mika; Halminen Olli; Mustonen Pirjo; Putaala Jukka; Linna Miika; Kinnunen Janne; Kouki Elis; Niiranen Jussi; Hartikainen Juha; Haukka Jari; Airaksinen Kari Eino Juhani (SPRINGER, 2022)
Atrial fibrillation (AF) is a major cause of ischemic stroke and the number of AF patients is increasing. Thus, up-to-date multifaceted data about the characteristics of AF patients, their treatments, and outcomes are urgently needed. The Finnish anticoagulation in atrial fibrillation (FinACAF) study has collected comprehensive data on all Finnish AF patients from 1st January 2004 to 31st December 2018. The aim of this paper is to describe the study rationale, the process of integrating data from the applied resources and to define the study cohort. Using national unique personal identification number, individual patient data is linked from nationwide health care registries (primary, secondary, and tertiary care), drug purchases, education, and socio-economic status as well as places of domicile, incomes, and taxes. Six regional laboratory databases (similar to 282,000, 77% of the patients) are also included. The study cohort comprises of a total of 411,000 patients. Since the introduction of the national primary care register in 2012, 9% of all AF patients were identified outside hospital care registers. The prevalence of AF in Finland-4.1% of whole population-is for the first time now established. The FinACAF study allows a unique possibility to investigate the epidemiology and socio-medico-economic impact of AF as well as the cost effectiveness of different AF management strategies in a completely unselected, nationwide population. This article provides the rationale and design of the study together with a summary of the characteristics of the cohort.